2016
DOI: 10.1016/j.ultrasmedbio.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The Imaging Modulography Technique Revisited for High-Definition Intravascular Ultrasound: Theoretical Framework

Abstract: Mechanical characterization of atherosclerotic lesions remains an essential step for the detection of vulnerable plaques (VPs). Recently, an intravascular ultrasound (IVUS) elasticity reconstruction method (iMOD) has been tested in vivo by our group. The major limitation of iMOD is the need to estimate the strain field in the entire VP despite attenuated depth penetration signals when using high-definition (HD) IVUS systems. Therefore, an extended iMOD approach (E-iMOD) was designed and applied to coronary les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…However, the estimated values were far from the actual ones. Similar outcomes were reported by Le Floc'h et al ( 2009) and Tacheau et al (2016) who successfully identified calcium inclusions but failed to accurately estimate their Young's modulus due to the small strains amplitudes. Nevertheless, the differences between considering the actual or the estimated Young's modulus did not affect the radial strains map.…”
Section: Figuresupporting
confidence: 85%
See 2 more Smart Citations
“…However, the estimated values were far from the actual ones. Similar outcomes were reported by Le Floc'h et al ( 2009) and Tacheau et al (2016) who successfully identified calcium inclusions but failed to accurately estimate their Young's modulus due to the small strains amplitudes. Nevertheless, the differences between considering the actual or the estimated Young's modulus did not affect the radial strains map.…”
Section: Figuresupporting
confidence: 85%
“…We computed the strains in both Cartesian and cylindrical coordinates, as well as the principal and equivalent strains. However, to be consistent with prior studies (Le Floc'h et al, 2009;Le Floc'h et al, 2012;Tacheau et al, 2016), we mainly utilized radial strains for the segmentation and optimization process due to their lower estimation error from IVUS images compared to other deformation variables.…”
Section: Neo Hooke Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…One promising approach is the iMOD elastography ( Le Floc’h et al., 2010 ), which developed several computational algorithms to rebuild elasticity strain maps inside the wall based on the prediction of the stress maps using IVUS-derived techniques. Since 2009, some remarkable improvements have been developed, such as two powerful stability plaque bio-markers of the coronary artery based on radial strains and its gradient, which allow Young’s modulus to be obtained under linear isotropic elasticity, plane strain, and incompressibility hypothesis ( Le Floc’h et al., 2009 ; Tacheau et al., 2016 ; Gómez et al., 2019 ). However, all these methods share a common issue: the waiting time between acquiring the image and obtaining the results from the computational model is prolonged due to the need to optimize the problem specific to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, complex non-linear geometric effects do not allow a direct correlation between the measured spatial strain field and the mechanical property of the tissue. By using the IVUS strain field inside atherosclerotic plaques (De Korte et al 2002;Doyley 2012;Maurice et al 2004aMaurice et al , 2007, several elasticity reconstruction approaches have been developed to characterize the entire lesion (Baldewsing et al 2007;Del eaval et al 2013;Doyley 2012;Le Floc'h et al 2009, 2012Nayak et al 2017;Poree et al 2017;Richards and Doyley 2011;Richards et al 2015;Tacheau et al 2016) and to delineate a subendoluminal layer of the arterial wall called the palpography domain (C espedes et al 2000;Del eaval et al 2013;Doyley et al 2001;Schaar et al 2005;Widynski et al 2014). Both techniques aim to characterize the mechanical properties of atherosclerotic lesions and ultimately differentiate vulnerable from stable plaques.…”
Section: Introductionmentioning
confidence: 99%